Evaluation and Assessment of the ABATE Framework to Enhance Implicit Bias Training for Virtual Interviews in Medical Schools - Veda Nagubandi; Caleb C. McKinney; Nicole M. Houle; Kristi D. Graves; Susan M. Cheng (Association of American Medical Colleges, 2024)
Introduction The influence of implicit biases in virtual interviews must be addressed to ensure equity within the admissions process. ABATE is a mnemonic framework of five specific categories of implicit bias (affinity-based, backdrop-based, appearance-based, technology and media-based, and enunciation-based biases) that should be anticipated and mitigated for faculty, staff, health professionals, and medical students who conduct virtual interviews at medical schools. Methods A 60-minute workshop was developed to educate medical school admissions interviewers about the ABATE model and strategies to mitigate implicit bias during virtual interviews. Four workshops were held over 1 year totaling 217 individual attendees. The workshops were evaluated using a single-group, pre-post questionnaire designed with the Kirkpatrick evaluation model. Results Attendees reported that they found the ABATE workshop useful and relevant to improving their ability to minimize implicit bias during virtual interviews. Significant improvements were found in attendee reactions to the utility of implicit bias training (M pre = 2.6, M post = 3.1, p = .002). Significant changes were also reported in attendees' attitudes about interviewing confidence (M pre = 3.0, M post = 3.2, p = .04), bias awareness (M pre = 3.0, M post = 3.4, p = .002), and identifying and applying bias mitigation solutions (M pre = 2.5, M post = 3.0, p = .003). Knowledge specific to backdrop-based biases also significantly increased (M pre = 3.2, M post = 3.4, p = .04). Discussion The ABATE workshop demonstrates promise in mitigating implicit bias in virtual medical school interviews.